Sleep bruxism in pediatric dental patients: an integrative review (Research, Society and Development, 2022)
The present study deals with sleep bruxism, also called nocturnal bruxism, or wakeful bruxism in pediatric dentistry patients, along with its characteristics and impacts on the child patient. Bruxism is defined as a repeated activity of the masticatory muscles, known as clenching or grinding the teeth, resulting in deleterious effects on the dentition, periodontium, masticatory muscles and temporomandibular joint. The etiology of sleep bruxism in children is considered multifactorial, associated with genetic, systemic, psychological factors and sleep or behavioral disorders. Dental surgeons and other health professionals should be aware of the signs and symptoms of sleep bruxism, therefore, in some situations, bruxism may be associated with oral problems such as: sensitivity/pain on palpation of the masticatory muscles, headache and symptoms. of temporomandibular disorder. Sleep bruxism should be common knowledge in the medical community in order to identify and refer the patient specialist. The diagnosis should be established based on possible etiological factors, and not only on clinical examinations. Treatment for this stereotyped and periodic movement disorder will be debatable, and individualized. The study aims to report about sleep bruxism in pediatric dentistry patients, etiology and proposed treatments for the parafunctional habit in question. In addition, to cover the impacts that these habits can cause. The articles were collected on the electronic platforms “PubMed” and “Science.gov”, referring to the topic in question, are in the publication period of 2015 to 2022.